2017
DOI: 10.1159/000484982
|View full text |Cite
|
Sign up to set email alerts
|

Waiting Time following Neoadjuvant Chemoradiotherapy for Rectal Cancer: Does It Really Matter

Abstract: Background: Neoadjuvant chemoradiotherapy (CRT) is considered the standard approach before any surgical intervention for locally advanced rectal tumors and has been proven to significantly improve the local recurrence rates of rectal cancer. However, the optimal timing of surgical resection after neoadjuvant CRT remains debatable. Objective and Methods: We conducted a retrospective review of 65 consecutive patients with locally advanced rectal cancer who underwent preoperative CRT followed by surgical resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Optimal timing of surgery after neoadjuvant chemoradiotherapy has been explored for cancer of other organs such as rectal and esophageal cancers. 15,[17][18][19][20][21][22] Longer intervals in rectal cancer have been associated with increased tumor downstaging and higher rates of a complete pathologic response. 23 However, this advantage is counterbalanced by concerns of poor outcomes because of local tumor progression or the development of metastatic disease during the extended interval.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal timing of surgery after neoadjuvant chemoradiotherapy has been explored for cancer of other organs such as rectal and esophageal cancers. 15,[17][18][19][20][21][22] Longer intervals in rectal cancer have been associated with increased tumor downstaging and higher rates of a complete pathologic response. 23 However, this advantage is counterbalanced by concerns of poor outcomes because of local tumor progression or the development of metastatic disease during the extended interval.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were also significant in patients experiencing fatigue post RT compared to non-fatigued patients. Other studies showed a rise in pro-inflammatory bacteria belonging to genus Sutterella (S. wadsworthensis and S. parvirubra) and decreased proportions of anti-inflammatory bacteria such as Faecalibacterium prausnitzii and Prevotella histicola, and additional members of the Firmicutes phylum, such as Lachnospira pectinoschiza, Roseburia intestinalis, and others [27,[60][61][62][63].…”
Section: Radiation Therapy Causes Gut Microbiota Dysbiosismentioning
confidence: 98%
“…Ideally, surgery should take place at the time of optimal response to preoperative nCRT as the effects of the latter are time dependent. [13]…”
Section: Introductionmentioning
confidence: 99%
“…Evidence also suggested that a waiting interval beyond 8 weeks might increase fibrosis around the TME plane, potentially lead to intra-operative technical difficulties, and higher surgical morbidity. [13]…”
Section: Introductionmentioning
confidence: 99%